The Seductive Chocolate Tastes in Statistical International Projection - Gabriela OPAIT (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2023)
The qualities of the dark chocolate guarantee for her consumers the refinement of the visual acuity and memory, the declin concerning the values of the hypertension, the values’s regression for the bad cholesterol, the levels’s setting regarding the triglycerides, the attention’s raise and a huge quantity of antioxidants and minerals. The target of this statistical travel in the chocolate galaxy consists in to estimate through forecasts, if between 2023-2025 will be a diminution of the values regarding the quantity of chocolate eated by each German, respectively any American from the U.S.A.